Automatication of Thickness Slice Measurement Using Non-Rotation Method on Three Ladder Objects from Computed Tomography - Dewi Angraini Insiano; Hasia Marto (Jurnal Penelitian Pendidikan IPA, 2025)
To perform slice thickness calculation automatically using the non-rotational method on the three ladder objects in the AAPM CT Performance Phantom image. Phantom was scanned with a GE Healthcare 128-slice CT scan scanner using slice thicknesses of 0.625 mm, 5.0 mm, and 10.0 mm. The software was developed with a non- rotational method to be able to measure the FWHM value and the mean on the three rungs of the object. In addition, the FWHM of the non-rotational method was compared with the rotational method The FWHM value from automatic measurement for slice thickness is 0.625 mm in three slice variations with non-rotational method 1.68 mm and rotation method 1.61 mm while for slice thickness 5.0 mm on non-rotation method is 6.51 mm, rotation method is 6.68 mm. , and for a slice thickness of 10.0 mm for the non-rotational method 9.58 mm and the rotational method 9.75 mm. The results of the non-rotational method were slightly lower (i.e. 1,74%) than the results of the rotational method for each nominal slice thickness, except for the smallest slicethickness The automatic slice thickness measurement algorithm on AAPM CT Performance Phantom has been improved using a non-rotational method. The improved algorithm can overcome the widening problem that occurred in the previous method due to object rotation.